Interpretative strategies and reading effects in the educational experience. Dissonances and Stimmungen of Unnatural Narrative (ENTHYMEMA, 2025)
This contribution aims to explore the experiential dimension of reading within the Unnatural paradigm, in order to compare literary criticism and literature education. Considering the imaginative and cognitive potential of highly dissonant plots, the objective is to verify, from a theoretical and application point of view, the hermeneutic strategies readers in the face of anti-mimetic inconsistencies in form and content. It will first be necessary to identify the main features of the Unnatural narrative and the main modes of reading it triggers according to theorists have deal with it. Subsequently, a didactic experiment will be designed to evaluate the effectiveness of an Unnatural narrative in educational settings. Readers' responses will be recorded for analysis and interpretation by considering specific cognitive categories. Finally, the study aims to operationalise both direct and indirect identification processes, in order to assess the extent of alignment – or divergence – with initial theoretical assumptions.
Keywords: Unnatural Narratology; Cognitive Dissonance; Literature Education; Stimmungen; Reading Effects